Historiozofie dziennikarskie. Na marginesie książki Na wschodnim posterunku. Księga pielgrzymstwa 1915-1918 Zygmunta Wasilewskiego (1919) - Kuciński, Paweł (Załącznik Kulturoznawczy, 2021)
The article describes the ideas of interpreting history and historical experience in the journalism of Zygmunt Wasilewski during World War I. History, initially surrounded by culturological categories, sociological and psychological methodology, eventually becomes political history. Related to the journalist’s predictions about Poland’s return to world maps. The concept of history and its interpretations evolve towards its political interpretations, which Wasilewski will use in his interwar writing period.